(untitled) (Journal of the College of Basic Education, 2023)
The importance of communication skills in the educational process in general and in teaching in particular comes fromIts role in facilitating the delivery of the message to the future if we look at the teaching process as a processA communication between the sender (the teacher) and the receiver (the student) to deliver a message (the study material).The concept is linked to the promotion of the human side in the educational process, as it is primarily a process and an exchange of ideas betweenPeople Both the student and the teacher are human beings who are inseparable from their human feelings and emotions.Educational studies presented a rich educational heritage in the research of teaching methods and their reflections onThe learners’ level of achievement, their love for the subject matter, or their emotional behavior, but the communication skillsIt was limited in the field of educational sciences, and the media people took advantage of it, considering it the basis of their specialization.However, communication skills are essential in all human life, especially educational, as they are related to broadcasting.Knowledge from minds to other minds seeking to convince the latter of them and diligently to invest these sciences.The researcher decided to conduct this study out of her belief that communication skills are necessary.In the education process, being “the transfer of knowledge of all kinds and different information from one person to another and frompoint to point and takes a path for it that usually starts from the source from which it originates to the one that receives it, thenIt bounces back to the source, and so on. These feedbacks take different forms that helpThe source is aware of the extent to which the objectives have been achieved, so he changes his message, its contents, and the way it is presented.and presenting them in a way that achieves the desired understanding” (Al-Tobji, p. 25) and her belief in the importance of these skillsFor the student/teacher before graduating from college and going to the field of work.. for this study to beempirically confirms the importance of enriching the educational lessons with practical exercises on communication skills so that they canEmployed in the first practical field encounter with students to be free of failures.The issue of systematic reinforcement with educational theories and sciences for students is an issue that is not in dispute.But the training-practical employment of these sciences is a more important issue because it will employ science in action.It is the goal of science.Through the foregoing, the researcher can determine the importance of the current study in:1. Emphasizing the importance of training in communication skills.